1974
DOI: 10.1128/aac.5.5.513
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Development of Resistance to Erythromycin, Other Macrolide Antibiotics, and Lincomycin in Mycoplasma pneumoniae

Abstract: Mycoplasma pneumoniae was made highly resistant to erythromycin in vitro by serial subculture in broth media containing erythromycin. The resistance developed to erythromycin was 200 Ag/ml with the Mac strain, a prototype of M. pneumoniae, and 10 ,g/ml with the Fukumura strain, an isolate. The erythromycin resistance was accompanied by cross resistance to other macrolide antibiotics (leucomycin, josamycin, spiramycin, and oleandomycin) and to lincomycin, but there was no resistance to vernamycin B. Resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Cross-resistance between macrolides and lincomycin has long been described (35,48), and cross-resistance was also reported between macrolides, pleuromutilins, lincomycin, and florfenicol (39,41). In the present study, the valnemulin-resistant MYC53 harboring mutations at positions 2035, 2060, 2500, and 2611 had elevated MICs to all of the tested 50S inhibitors.…”
Section: Discussionmentioning
confidence: 48%
“…Cross-resistance between macrolides and lincomycin has long been described (35,48), and cross-resistance was also reported between macrolides, pleuromutilins, lincomycin, and florfenicol (39,41). In the present study, the valnemulin-resistant MYC53 harboring mutations at positions 2035, 2060, 2500, and 2611 had elevated MICs to all of the tested 50S inhibitors.…”
Section: Discussionmentioning
confidence: 48%
“…Treatment with erythromycin results in relatively rapid alleviation of symptoms; however, viable M. pneumoniae can frequently be isolated from infected individuals for a prolonged period of time following therapy (6,41,45). Isolation of resistant strains from patients following treatment is not uncommon (26,28,(43)(44)(45), and erythromycinresistant mutants are readily derived by selection in vitro (27,43,44). Phenotypic studies have demonstrated that most of these strains simultaneously developed resistance to macrolide, lincosamide, and group B streptogramin (MLS) antibiotics (48).…”
mentioning
confidence: 99%
“…Niitu et al reported the development of erythromycin resistance in M. pneumoniae that was accompanied by cross-resistance to other macrolide antibiotics in vitro; they also reported the isolation of M. pneumoniae that was resistant to erythromycin and other antibiotics after erythromycin therapy (14,15). New quinolones might exhibit antimycoplasmal activity against macrolide-and tetracycline-resistant strains of M. pneumoniae because of their different mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…Macrolide and tetracycline antibiotics have been widely used in chemotherapy against M. pneumoniae infections because of the susceptibility of the infectious agent to these antibiotics (1,4,13,17,23). At the same time, the reported incidences of mutants resistant to erythromycin from patients treated with or without the antibiotics have increased (14,15).Recently, the efficacy of new quinolones against various respiratory pathogens, including M. pneumoniae, has been demonstrated (4,16,22). We have also reported that temafloxacin, ofloxacin, and ciprofloxacin, among several new quinolones, possess more mycoplasmacidal activity against M. pneumoniae than macrolide and tetracycline antibiotics.…”
mentioning
confidence: 98%
See 1 more Smart Citation